Theoretisieren als Partisanenarbeit: Zum Politikum subversiven Denktuns am Exempel Johannes Agnoli (22.2.1925-4.5.2003) - Narr, Wolf-Dieter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
The article reminds of Johannes Agnoli, one of the most important marxist authors on state and politics in Germany. Some of the most central issues in his work are shortly presented: the connection of subversion and utopia, the kind of critique Agnoli proceeds, critique not only of certain policies but of politics as a certain social form including the critique of the party-form of left engagement, and the irony Agnoli thought a revolutionary needs in non-revolutionary times.